2015
DOI: 10.1016/j.physbeh.2015.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment decreases daily salt intake and prevents heart dysfunction following subchronic aortic regurgitation in rats

Abstract: Depression is a predictor of poor prognosis in patients with heart failure. Selective serotonin (5-HT) reuptake inhibitors (SSRIs) may improve these outcomes. Left ventricular volume overload induced hypertrophy that is associated with aortic regurgitation (AR) leads to ventricular dysfunction and heart failure. The aim of this study was to verify the effects of the SSRI paroxetine on cardiac function, as well as on fluid intake and excretion, in subchronic AR. Male Wistar rats (260 to 280g) received sham (SH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…4). In rats, low Na also indicates depression, and antidepressant treatment may reduce salt intake (102,103) . The relationship of salt intake and mood is examined briefly below.…”
Section: Adult Salt Intakementioning
confidence: 99%
See 1 more Smart Citation
“…4). In rats, low Na also indicates depression, and antidepressant treatment may reduce salt intake (102,103) . The relationship of salt intake and mood is examined briefly below.…”
Section: Adult Salt Intakementioning
confidence: 99%
“…In animal studies, salt was found to mitigate stress and facilitate social behaviour, which are useful effects, while low Na and its related hormones were found to indicate depression (2,55,102,103,126) . The human data are less consistent.…”
Section: Conditioning Salt Preference Through Exertion Mood Health mentioning
confidence: 99%
“…Male Wistar rats (260 to 280 g) had sham or AR surgeries induced by multiple retrograde puncture of the aortic valve leaflets under anesthesia (ketamine 80 mg/kg of bw plus xylazine 7mg/Kg bw, Vetbrands, Jacareí-SP) as described elsewhere 24,25,26 . All procedures were in accordance with the Animal Care and Use policies of the Institute of Biosciences of Botucatu, according to the Brazilian College of Animal Experimentation (COBEA, number 141/09) policies.…”
Section: Animal Model Of Armentioning
confidence: 99%
“…Animals that failed to meet these criteria were excluded. We analysed LV dimensions, wall thickness, ejection fraction, diastolic function, and cardiac output (i.e., ejection volume in the LV outflow tract-heart rate), as previously reported 24,25,26 .…”
Section: Echocardiographymentioning
confidence: 99%
“…In animal models, the association between excessive salt intake and cognitive impairment were observed in experimental studies . Liu et al found that a high‐salt diet significantly impaired the spatial memory of C57BL/6J mice .…”
Section: Association Of Cognitive Impairment With Inflammatory Conditmentioning
confidence: 99%